THE ANALYSIS OF ADDITIONAL VALUE OF BROWN-PALM-SUGAR AGROINDUSTRY IN Kolaka - Rianse, Ilma Sarimustaqiyma; Hartono, Slamet; suryantini, Any; Jamhari, Jamhari; Darwanto, Dwidjono Hadi; Widodo, Sri; Waluyati, Lestari Rahayu (International Journal of Sustainable Tropical Agricultural Sciences, 2015)
AbstractBrown-palm-sugar agroindustry in Kolaka is an industrial model that tends to have a simple character for moldable sugar processing. Moldable brown palm sugar is produced by processing of unfermented palm-juice. Its processing into brown-palm-sugar can provide additional value as reward for the usage of production factors. The additional value is multiplier effect that occurs in an agroindustrial activity. The strategical role of agroindustry that relies on increasing of the additional value of domestic natural resource potency is believed to be capable of supporting in national competitive improvement.This study is objected (1) to recognize the additional-valuable amount in processing unfermented palm-juice into brown palm sugar; (2) to determine the influence factors in brown-palm-sugar additional value. Additional value analysis which was using hayami method demonstrates that the additional value whose craftsmen of unfermented-palm-juice into brown-palm-sugar process received is 696.51 rupiahs per kilogram. The other input prices (such as the price of palm oil, lime price and firewood) and labor costs significantly and negatively effected on the additional value, while the output price significantly and positively effected. And then, the price of unfermented palm-juice unsignificantly effect on the additional value.Keywords: agroindustry; brown palm sugar; additional value